PENYULUHAN PENYAKIT DEGENARATIF DAN PEMERIKSAAN KESEHATAN DI PONDOK PESANTREN AT TAUFIQ KOTA MALANG - Siti Munfaqiroh; Yuyuk Liana (Jurnal Pengabdian kepada Masyarakat, 2020)
Degenerative disease is a disease that needs special attention because with age, the functions of the organs of the body begin to decline. In connection with this, Community Service in the form of counseling about degenerative diseases and conducting health checks on local residents. This activity was carried out as a form of collaboration between STIE Malangkucecwara and LKSA At Taufiq Islamic Boarding School. The main goal is that residents gain sufficient insight and knowledge about degenerative diseases and know how to handle them. It is hoped that this counseling and examination will create people who are more alert and have a high awareness of health for a better life in the future.